Anterior thalamic deep brain stimulation in refractory epilepsy: A randomized, double‐blinded study. (11th December 2018) - Herrman, Helle; Egge, Arild; Konglund, Ane E.; Ramm‐Pettersen, Jon; Dietrichs, Espen; Taubøll, Erik
Abstract : Objectives: The safety and effect on seizure frequency of anterior thalamic nucleus deep brain stimulation were studied in this prospective, randomized, double‐blinded study. Patients were followed for 12 months. The first 6 months were blinded with regard to active stimulation or not. After 6 months, all patients received active stimulation. Material and methods: Bilateral ANT electrodes were implanted into 18 patients suffering from focal, pharmacoresistant epilepsy. Antiepileptic treatment was kept unchanged from three months prior to operation. The Liverpool seizure severity scale (LSSS) was used to measure the burden of epilepsy. Results: There was no significant difference between the 2 groups at the end of the blinded period at 6 months. However, when considering all patients and comparing 6 months of stimulation with baseline, there was a significant, 22% reduction in the frequency of all seizures ( P = 0.009). Four patients had ≥50% reduction in total seizure frequency and 5 patients ≥50% reduction in focal seizures after 6 months of stimulation. No increased effect over time was shown. LSSS at 6 months compared to baseline showed no significant difference between the 2 groups, but a small, significant reduction in LSSS was found when all patients had received stimulation for 6 months. Conclusions: Our study supports results from earlier studies concerning DBS as a safe treatment option, with effects even in patients with severe, refractory epilepsy. However, our results are not as encouraging as those reported from many other, mainly unblinded, and open studies.